Pengembangan Potensi Ekowisata Desa Malasari, Kecamatan Nanggung Kabupaten Bogor - Heryanti Utami (Fakultas Pariwisata Universitas Pancasila, 2017)
Malasari village is a village located within the Halimun Salak Mountain National Park. For years, people have been using the National Park area for the sake of livelihood, especially with regard to forest products. However, in later development, tourism becomes an alternative solution for the people of Malasari Village. The purpose of this study was to determine the extent of tourism potential and the direction of tourism development at Malasari Village. This study used qualitative approach with descriptive analytical method. Collecting data using interviews and observations in the field. The collected data were analyzed qualitatively. The results showed that the tourism potential that can be developed in Malasari Village is not only the nature-based tourism related to its existence inside Mount Halimun Salak National Park but also cultural tourism, rural tourism, educational and special interests tourism. Based on the results, hencer further research is needed to develop tourism development strategy for Malasari which includes the promotion strategy and partnership of government, private and public.